Laboratorijski priročnik za delo z rastlinskimi tkivnimi kulturami, s poudarkom na mikropropagaciji: laboratorij za fiziologijo rastlin - Ambrožič-Dolinšek, Jana (2017)
Laboratory Manual for Plant Tissue Culture, with an Emphasis on Micropropagation: Laboratory for Plant Physiology. The laboratory manual was prepared for those who are entering the world of plant tissue culture and starting to work in this field of plant biotechnology. It is devoted to the study process and subjects associated with plant tissue culture and micropropagation. It will answer the following questions: "What is tissue culture? How it is connected with plants? Is micropropagation something I can do and that I know how to do? How do I deal with this?" The basic techniques are introduced, along with examples. It includes a terminology glossary with definitions of the terms used in the text.
Keywords: laboratory manual; plant; tissue culture; micropropagation